Statistics of the antenna arrays field with heterogeneous errors (Average antenna characteristics) - Корниенко, Л.Г. (Radiotekhnika, 2020)
A methodology for studying the directional properties of antenna arrays with heterogeneous (in dispersion) errors in the excitation and placement of radiators is described. Mechanisms of origin and the mathematical model of heterogeneous errors are determined. Features and differences in statistical effects inherent in the average antenna characteristics of heterogeneous and uniform errors are revealed. General properties of the average power radiation pattern (RP), represented as an expansion into coherent and scattered components, for arbitrary antenna arrays, error values, and their distribution law are investigated. The coherent component does not depend on the correlation properties of errors and is formed by a statistical amplitude-phase distribution (APD), the differences of which from a regular APD depend on the degree of error heterogeneity. The degree of error correlation affects the directional properties of the dissipated power. For completely correlated errors, the average RP does not coincide with the RP in the absence of errors. Numerical results are given for linear antenna arrays and three types of heterogeneous phase errors with increasing/decreasing dispersion towards the edges of the antenna and its two-level value. A criterion for the equivalence of heterogeneous phase errors by the intensity of their impact on the radiated fields is selected. The analysis of the average RP, the limiting average level of lateral radiation was carried out using a generalized angular variable, which allowed us to extend the results to antenna arrays with transverse, inclined, and axial radiation with different electric sizes and steps, as well as compare them with continuous radiated systems and determine the areas where the results coincide. The question of the average directive gain (DG) is studied. For antenna arrays with axial radiation, the optimal relations are determined to achieve its maximum value, taking into account the type of heterogeneous phase errors, their correlation properties, and the antenna arrays spacing. It is shown that it is advisable to take into account the properties of error heterogeneity in the statistical analysis of the antenna field, since the nature of their influence on the directional and energy parameters of the array and its sensitivity depends significantly on their type and amplitude distribution. The types of phase errors causing increased distortion of the average characteristics are determined. The obtained theoretical data generalize the results of the theory of antenna arrays with uniform errors and supplement them with new ideas about the characteristics of random fields and ways of practical use of research results.